A Comparative Study between Learning Organizartional Framework and UAE GOvernment Initiative - Nowduri, Srinivas (Archives of Business Research, 2020)
This research work compares the learning organizational framework with that of UAE government proposed initiatives towards its academic institutions from three different perspectives viz., 1. Four pillars of modern organizations 2. Different layers of fostering a learning culture 3. The life cycle of a high-performance learning organizations. A comparative study is made between learning organizations initiates and UAE proposed initiatives. Finally concluded with few influencing factors of UAE economy from academy perspective.